Design of multi-epitope peptides containing HLA class-I and class-II-restricted epitopes derived from immunogenic Leishmania proteins, and evaluation of CD4+ and CD8+ T cell responses induced in cured cutaneous leishmaniasis subjects - Hamrouni, Sarra; Bras-Gonçalves, Rachel; Kidar, Abdelhamid; Aoun, Karim; Chamakh-Ayari, Rym; Petitdidier, Elodie; Messaoudi, Yasmine; Pagniez, Julie; Lemesre, Jean-Loup; Meddeb-Garnaoui, Amel (PLoS neglected tropical diseases, 2020)
Human leishmaniasis is a public health problem worldwide for which the development of a vaccine remains a challenge. T cell-mediated immune responses are crucial for protection. Peptide vaccines based on the identification of immunodominant T cell epitopes able to induce T cell specific immune responses constitute a promising strategy. Here, we report the identification of human leukocyte antigen class-I (HLA-I) and -II (HLA-II)-restricted multi-epitope peptides from Leishmania proteins that we have previously described as vaccine candidates. Promastigote Surface Antigen (PSA), LmlRAB (L. major large RAB GTPase) and Histone (H2B) were screened, in silico, for T cell epitopes. 6 HLA-I and 5 HLA-II-restricted multi-epitope peptides, able to bind to the most frequent HLA molecules, were designed and used as pools to stimulate PBMCs from individuals with healed cutaneous leishmaniasis. IFN-γ, IL-10, TNF-α and granzyme B (GrB) production was evaluated by ELISA/CBA. The frequency of IFN-γ-producing T cells was quantified by ELISpot. T cells secreting cytokines and memory T cells were analyzed by flow cytometry. 16 of 25 peptide pools containing HLA-I, HLA-II or HLA-I and -II peptides were able to induce specific and significant IFN-γ levels. No IL-10 was detected. 6 peptide pools were selected among those inducing the highest IFN-γ levels for further characterization. 3/6 pools were able to induce a significant increase of the percentages of CD4+IFN-γ+, CD8+IFN-γ+ and CD4+GrB+ T cells. The same pools also induced a significant increase of the percentages of bifunctional IFN-γ+/TNF-α+CD4+ and/or central memory T cells. We identified highly promiscuous HLA-I and -II restricted epitope combinations from H2B, PSA and LmlRAB proteins that stimulate both CD4+ and CD8+ T cell responses in recovered individuals. These multi-epitope peptides could be used as potential components of a polytope vaccine for human leishmaniasis.